Pepper SBP-box transcription factor, CaSBP13, plays a negatively role in drought response - Zhang, Huai-Xia; Zhang, Yuan; Zhang, Bo-Wen (Frontiers in Plant Science, 2024)
The SBP-box gene is instrumental in plant growth, development, and stress responses, yet its role remains elusive in pepper plants during drought stress. In this research, we identified a CaSBP13 gene from pepper genomic data. Its upregulation was observed following drought treatments. Silence of CaSBP13 in pepper markedly enhanced drought resistance, observed as diminished active oxygen levels. Additionally, the water loss rate, relative electrical conductivity, malondialdehyde content, and stomatal density were lower in CaSBP13-silenced plants compared to controls. Conversely, CaSBP13 overexpression in Nicotiana benthamiana reduced drought tolerance with increased reactive oxygen levels and stomatal density. Moreover, crucial genes in the ABA signaling pathway (CaPP2C, CaAREB) displayed reduced expression levels in CaSBP13-silenced plants post drought stress, compared to control plants. Conversely, CaPYL9 and CaSNRK2.4 demonstrated augmented expression in CaSBP13-silenced plants under similar conditions. ConverselyHowever, a reverse pattern for NbAREB, NbSNRK2.4, and NbPYL9 was observed post-four day drought in CaSBP13-overexpression plants.a converse trend regarding NbAREB, NbSNRK2.4, and NbPYL9 was seen after four days of drought stress in CaSBP13-overexpressing plants. These findings suggest that CaSBP13 negatively modulates drought tolerance in pepper, possibly through reactive oxygen species (ROS) and ABA signaling pathways.